THE IMPACT OF THE ACCOUNTING POLICIES ON THE SHARE PRICES OF COMPANIES AND BANKS - Malgorzata Bialas (European Scientific Journal, ESJ, 2013)
This article concerns the impact of accounting policies on the share price of companies and banks in Poland. The article draws attention to the profit and loss account, which contains an increasing number of records that are not a reflection of actual operations, but for example the valuation of balance sheet items in fair value. Therefore, the result which is calculated on an accrual basis is different from the result calculated on cash basis. The study shows the degree of differences between the results in the profit and loss account and the results in the cash flow statement. It is noted that the degree of differences for banks is lower than in the case of companies. Then the correlation coefficient between changes in stock prices and the gap between the income statement and cash flow statement is calculated. It is shown that the correlation coefficient is very weak.